RANCANG BANGUN MESIN PENGIRIS UBI KAYU MENGGUNAKAN PENDEKATAN NORDIC BODY MAP (NBM) DAN PENDEKATAN ANTROPOMETRI - SALEH, ABDUL RAHMAN (Jurnal TIN Universitas Tanjungpura, 2017)
Cassava is one of the farm’s product that is located in West Kalimantan, especially in Sekadau District. In Mr. Abu’s home industry of cassava chips which it used manual cutting tool, the cutting process often got pain on skeletal muscle such us waist, brisket, necklace, arm, and got work accident because position was not ergonomic. Based on problems, the solution that can do is using cassava cutting machine design. Therefore, this research is needed to decrease pain problems and work accident in the cutting process of cassava. The method that was used in this research is Nordic Body Map with antropometri approach. Nordic Body Map is the method of subject assessment which the results depend on condition who is gotten by worker to know the level of injury risk on moskuleskeletal system. Antropometric was used to determine the size of machine which it will be built depends on operator body dimention. In order to the cassava cutting machine will be ergonomic and can improve the result of operator work. The results showed that the using method of Nordic Body Map got the low level of injury risk on muscle in amount of 458,75%. The comparasion result in before and after designing increases in amount of 105 %. The dimention of choosing machine is the height of seat of 45 cm, the height of back seat of 53 cm, the height of machine of 97 cm, the depth of back seat of 47 cm, the depth and length maximum of machine around from 73 cm. Keyword – Antropometry, Cutting Machine Cassava, Design, Ergonomy, Nordic Body Map.